2014
DOI: 10.1007/s12273-014-0197-0
|View full text |Cite
|
Sign up to set email alerts
|

Energy and climate simulation in the Upper Lawn Pavilion, an experimental laboratory in the architecture of the Smithsons

Abstract: This article aims to provide a critical analysis of the work of the Smithsons, with a focus on its interpretation of architecture from the standpoint of environmental commitment, an aspect that is barely touched upon in the extensive literature analysing their work. The main aim is to reveal the strategies of environmental conditioning and the energy behaviour of their major work both from an architectural and environmental standpoint, as well as that of their own home and experimental laboratory: the Upper La… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 5 publications
0
5
0
1
Order By: Relevance
“…Upper Lawn Pavilion (Great Britain) [7] Dynamic energy simulation Environmental design-based results reveal deficient behaviour in need of updating in order to comply with current standards.…”
Section: Case-study Methods Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Upper Lawn Pavilion (Great Britain) [7] Dynamic energy simulation Environmental design-based results reveal deficient behaviour in need of updating in order to comply with current standards.…”
Section: Case-study Methods Resultsmentioning
confidence: 99%
“…As a result, this housing is protected by laws designed to preserve its appearance. Housing architecture of the Modern Movement constituted a departure from earlier trends and increased awareness of issues relating to energy [7].…”
Section: Introductionmentioning
confidence: 99%
“…In this line, complex simulation tools, such as DesignBuilder, can be useful to evaluate building performance. Studies have reported its usefulness in confirming that, in some examples of good architecture, the buildings' environmental performance is far from the current standards of adaptive comfort [76].…”
Section: Bibliography Analysismentioning
confidence: 95%
“…Nonetheless, these strategies aimed at obtaining better buildings have not received the official support of the Governments as there are few examples of regulations, i.e., ASHRAE 55 [24] and EN 16798 [25], that specifically address the evaluation of comfort. The lack of transversal methods to evaluate energy efficiency and comfort has opened a debate, and there are examples of research aimed at finding common strategies to improve both fields [1,26,27]. In the case of Spain, comfort conditions are contained within the regulations that define the minimum requirements for the conditioning of interior spaces, although there is no specific evaluation method, and only minimum and maximum values for temperature, relative humidity, and ventilation are set.…”
Section: Evaluation Of Comfortmentioning
confidence: 99%